Growth dynamics and space in Brazil - Mariano Mossi; Patricio Aroca; Ismael Fernandez; Carlos Azzoni (European Regional Science Association (ERSA), 2002)
This paper takes up some of the newly developed tools of spatial econometrics to analyse the importance of geography in regional growth. This perspective is used to characterise growth features in the Brazilian economy. Two strands of empirical literature are brought together to draw the picture of geography as a factor affecting differential economic performance. Firstly, spatial statistics tradition is implemented to examine the spatial dependence of regional per capita income in Brazil for the last six decades. Secondly, the role that geography may have on the determination of growth paths is approached using intradistribution dynamics tools based on the construction of Markov transition matrices and stochastic kernels, for discrete and continuous analysis respectively.
Keywords: 330